Induced Chromosomal Proximity and the Genesis of Gene Fusions in Prostate Cancer - Mani, Ram-Shankar (2009)
Gene fusions have a critical role in cancer progression. Mechanisms associated with the genesis and cell type specificity of these fusions are not well understood. A prototypical gene fusion, TMPRSS2-ERG, involves the 5’ untranslated region of the androgen-regulated gene TMPRSS2 with the ERG gene, and is the most common gene fusion associated with prostate cancer. We demonstrate that androgen signaling induces chromosomal proximity between TMPRSS2 and ERG loci, and facilitates the formation of the TMPRSS2-ERG gene fusion when subjected to an agent that causes DNA double strand breaks. These results provide a conceptual framework for the genesis of gene fusions and may provide suggestions as to the general etiology of human prostate cancer.